PERUBAHAN PARADIGMA PENDIDIKAN ISLAM: APLIKASI ICT DALAM PROSES PEMBELAJARAN PAI DI SEKOLAH - Ahmad Zainuri (Conciencia, 2017)
The use of ICT as a medium of learning and teaching needed to realize the effectiveness and optimization of learning. But be aware that regardless of the medium used learning principles are upheld. It must be recognized that there are still many teachers who "technology illiterate" and must be improved further educational qualifications and professionalism. And that is also the problem is the low level of use of ICT in schools (digital divide) whereas ICT can support the optimization of the school, because of the potential of ICT is quite large. Application of ICT in learning PAI, if carried out by PAI teacher, it will have a positive impact on the interest of students towards subjects PAI in school. So that students in the following subjects PAI is not forced, but self-consciousness. In addition, if the PAI learning in the classroom, teachers use ICT, this will spread the "virus positive" on the teachers of other subjects, so they do the same thing